SOSIALISASI HUKUM DALAM KEHIDUPAN MASYARAKAT - Muhammad Mahrus Ali (university Of islam, 2021)
The progress of a nation can be seen from the level of legal awareness of its citizens. The higher the legal awareness of the population of a country, the more orderly the life of society and state will be. This research has a problem formulation: What is the importance of legal socialization in society? What are the inhibiting factors for the socialization of law in society? Basically, the Indonesian people know and understand the law, but they are also consciously committing acts that violate the law. Narcotics users and dealers know that consuming and distributing narcotics against the law is a criminal act, but the fact is that the act is still being committed. The legal awareness of the Indonesian people is still weak which is synonymous with lawlessness. The next factor is the means or facilities that support law enforcement. Without certain means or facilities, it is impossible for the efforts to eradicate narcotics crime to proceed smoothly. These facilities or facilities include, among others, human resources, good organization, adequate equipment and space, adequate finance, and so on.